The larva of Palaemnema mutans Calvert, 1931 (Odonata: Platystictidae) - Amaya-Vallejo, Vanessa; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2011)
The larva of Palaemnema mutans is described, illustrated, and compared with larvae of the genus described to date. P. mutans differs from the other species in having a shorter body length, a larger number of teeth in the internal molar lobe of the left mandible and shorter caudal lamellae, as well as an apical filament proportionally longer than in any other species. The hypopharynx is described for the first time for the genus. This is the first record of P. mutans for Colombia.